Enhance of tomato production and induction of changes on the organic profile mediated by Rhizobium biofortification - Gen-Jiménez, Adriana; Flores-Félix, José David; Rincón-Molina, Clara Ivette; Manzano-Gomez, Luis Alberto; Rogel, Marco Antonio; Ruíz-Valdiviezo, Víctor Manuel; Rincón-Molina, Francisco Alexander; Rincón-Rosales, Reiner (Frontiers in Microbiology, 2023)
Introduction The extensive use of chemical fertilizers has served as a response to the increasing need for crop production in recent decades. While it addresses the demand for food, it has resulted in a decline in crop productivity and a heightened negative environmental impact. In contrast, plant probiotic bacteria (PPB) offer a promising alternative to mitigate the negative consequences of chemical fertilizers. PPB can enhance nutrient availability, promote plant growth, and improve nutrient uptake efficiency, thereby reducing the reliance on chemical fertilizers. Methods This study aimed to evaluate the impact of native Rhizobium strains, specifically Rhizobium calliandrae LBP2-1, Rhizobium mayense NSJP1-1, and Rhizobium jaguaris SJP1- 2, on the growth, quality, and rhizobacterial community of tomato crops. Various mechanisms promoting plant growth were investigated, including phosphate solubilization, siderophore production, indole acetic acid synthesis, and cellulose and cellulase production. Additionally, the study involved the assessment of biofilm formation and root colonization by GFP-tagged strains, conducted a microcosm experiment, and analyzed the microbial community using metagenomics of rhizospheric soil. Results The results showed that the rhizobial strains LBP2-1, NSJP1-1 and SJP1-2 had the ability to solubilize dicalcium phosphate, produce siderophores, synthesize indole acetic acid, cellulose production, biofilm production, and root colonization. Inoculation of tomato plants with native Rhizobium strains influenced growth, fruit quality, and plant microbiome composition. Metagenomic analysis showed increased Proteobacteria abundance and altered alpha diversity indices, indicating changes in rhizospheric bacterial community. Discussion Our findings demonstrate the potential that native Rhizobium strains have to be used as a plant probiotic in agricultural crops for the generation of safe food and high nutritional value.